Associations between fitness, movement behaviors, and immediate post-exercise blood pressure in older adults: A network perspective - Gabriel Costa Souto; Ana Clara Cassimiro Nunes; Rodrigo Alberto Vieira Browne; Yuri Alberto Freire; Paulo Felipe Ribeiro Bandeira; Eduardo Caldas Costa (PLoS ONE, 2025)
Understanding the associated factors of immediate post-exercise blood pressure, a proxy for exercise blood pressure, is relevant for improving cardiovascular risk assessment and guiding interventions. This study investigated associations between fitness and movement behavior components with immediate post-exercise blood pressure in older adults using network analysis. In this cross-sectional study, 237 older adults (66 ± 5 years), without known cardiovascular disease were included. Blood pressure was measured before and immediately after a 3-minute moderate walking test (5 METs). Moderate-to-vigorous physical activity and sedentary time were assessed using hip-worn accelerometers for one week. Proxies for fitness were: six-minute walking test, handgrip strength, and 30-second sit-to-stand test. Network analysis, a multivariate statistical approach which captures interrelations among multiple variables within a system, was used to examine direct and indirect associations between fitness, movement behaviors, and post-exercise blood pressure. Lower handgrip strength (weight: −0.136) and 30-second sit-to-stand (weight: −0.106) performances were directly associated with greater immediate post-exercise blood pressure, indicating that reduced muscular strength is linked to greater cardiovascular load after exertion. Lower handgrip strength (weight: −0.176) and reduced physical activity (weight: −0.128) were directly associated with higher resting BP, which in turn had the strongest direct association with immediate post-exercise blood pressure (weight: 0.581), suggesting an indirect pathway through resting blood pressure. Centrality indicators suggested six-minute walking test, 30-second sit-to-stand test, and sedentary time as potential interventions targets, moderate-to-vigorous physical activity as a central hub within network, and handgrip strength as a highly connected node. Our findings suggest a complex interplay – both direct and indirect (via resting blood pressure) – between fitness, movement behaviors, and immediate post-exercise blood pressure in older adults. Increasing moderate-to-vigorous physical activity, cardiorespiratory fitness, and muscle strength, along with reducing sedentary time, may be potential targets for attenuating immediate post-exercise blood pressure in this age group.